On classification of real hypersurfaces in a complex space form with eta-recurrent shape operator - Loo, T.H. (Tokyo Journal Mathematics Editorial Office Acad Center, 2014)
In this paper, we classify real hypersurfaces in a non-flat complex space with eta-recurrent shape operator